Analisis Model Bisnis di Pasar Kamu Kabupaten Deli Serdang MenggunakanPendekatan Business Model Canvas - Cahyadi, Ferry; Simanjuntak, Tri Handayani; Samosir, Kristin Jesika; Zega, Hatta Adisaro (CV. Kurnia Grup, 2025)
This study aimed to analyze the business model of Pasar Kamu Kampung Lama in Deli Serdang Regency using the Business Model Canvas (BMC) approach. Pasar Kamu is a community-based traditional market that plays an important role in supporting the local economy and preserving social and cultural values. However, its management system had not been structured comprehensively, particularly in terms of marketing strategies and business development. This research employed a qualitative descriptive method. Data were collected through in-depth interviews, direct observation, and documentation involving market managers, traders, and visitors. The results indicated that Pasar Kamu possessed strong value propositions based on local products, affordable prices, and close social relationships between sellers and customers. Nevertheless, several BMC elements, such as marketing channels, strategic partnerships, and the utilization of digital media, had not been optimally developed. The study concluded that the Business Model Canvas was effective in mapping the overall business condition of Pasar Kamu and could serve as a strategic foundation for developing sustainable community-based traditional markets.